EXPLORING THE USE OF EVIDENCE BASED HEALTHCARE DESIGN IN SOUTH AFRICA USING COLOUR, LIGHT AND BIOPHILIA TO UNDERSTAND THE EFFECTS OF INTERIOR DESIGN ON THE PERCEIVED RECOVERY AND WELLBEING OF PATIENTS IN HOSPITALS - Lutchmans, Reshaelen (The IIE, 2022)
Our daily surroundings and the environments we are in everyday profoundly influence our physical and psychological wellbeing (Waller & Finn, 2004). Healthcare facilities have for many years been designed and focused on creating hygienic safe spaces as well as functionality; however in the 21st-century healthcare facilities need to focus on the overall well-being of the patient. The question is, does the current design of hospitals stimulate or regress patient perceived recovery/outcome. This study is an exploration of improving Health Care Facilities (HCF) specifically in SA, through EBHD as the foundation theory/concept, and incorporating Color Theory, Light theory and Biophilic Design to aid in the perceived recovery process as well as the overall well-being of patients, while also exploring healing environments. For this qualitative research the researcher utilized a cross-sectional timeline for secondary research methodology using 3 data-collection methods specifically: observation, documentation, and records(Lalehzari, 2021). Cintocare Hospital and Netcare Sunninghill Hospital are the two hospitals studied and analysed against a set list of criteria (Figure 1: List of Criteria). A visual analysis was conducted at both facilities and the design discussed detailed. Common themes or similarities and variances are identified between the two analysed facilities. It is then determined if the design of the two hospitals are informed by EBHD and the percentage thereof. The study was limited by the Novel Coronavirus (COVID-19) pandemic and the government imposed restriction of movements to curb the spread of the virus. Based on this the researcher was unable to answer the research question as access to medical facilities were hindered. However from the data collected, it can be deduced that the design of a HCF has a direct impact on the recovery and overall well-being of patients. From the research activities, it is evident that there is a definitive and much needed transformation of design in the creative consideration in the development of medical facilities and hospitals.
Keywords: Color; Emotions; Psychology